![2x-2=-x+10](https://img.qammunity.org/2023/formulas/mathematics/college/im6hjsznq3l823j4snammfb0eef81c4xv8.png)
To solve this question you need to leave in one side of the equal all the terms with the variable (x) and in the other side the other terms:
- Add x in both sides of the equation
![\begin{gathered} 2x+x_{}-2=-x+x+10 \\ 3x-2=10 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/awzisqrkdnf4a1qgnxat19chsurozj2fn9.png)
-Add 2 in both sides of the equation:
![\begin{gathered} 3x-2+2=10+2 \\ 3x=12 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/gwhwz4iip4az8hrbrva8m7a2bnz4986zqx.png)
-Divide into 3 both sides of the equation:
![\begin{gathered} (3)/(3)x=(12)/(3) \\ \\ x=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/azaz9nsoy4ox1h18pp4w0nh0myni4meeil.png)
Then, the solution for the given equation is x=4